2008
DOI: 10.1021/jm701600a
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Antimicrobial Peptidomimetics with Therapeutic Potential

Abstract: A series of synthetic antimicrobial peptidomimetics (SAMPs) have been prepared and found to be highly active against several Gram-negative and Gram-positive bacterial strains. These derivatives comprise the minimal structural requirements for cationic antimicrobial peptides and showed high selectivity for Gram-negative and/or Gram-positive bacteria compared to human red blood cells. We have found that SAMPs share many of the attractive properties of cationic antimicrobial peptides inasmuch that a representativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
144
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(150 citation statements)
references
References 48 publications
3
144
0
Order By: Relevance
“…1). As a result, this peptide is active against Staphylococcus epidermidis, a welldescribed biofilm producer associated with device-related infections (20,29). Similar Arg-X-Arg molecules were created during research of protease susceptibility; the most active derivative contained a bulky para-phenyl naphthalene (PPN) substitution as the variable component (69).…”
Section: Increasing Activitymentioning
confidence: 99%
“…1). As a result, this peptide is active against Staphylococcus epidermidis, a welldescribed biofilm producer associated with device-related infections (20,29). Similar Arg-X-Arg molecules were created during research of protease susceptibility; the most active derivative contained a bulky para-phenyl naphthalene (PPN) substitution as the variable component (69).…”
Section: Increasing Activitymentioning
confidence: 99%
“…LTX-109 (Lytixar; Lytix Biopharma AS, Oslo, Norway) is one such novel SAMP which rapidly kills bacteria via membrane disruption and has not been associated with cross-resistance to other available drugs. LTX-109 has also been shown to have a low propensity for the development of resistance (5,6,8).…”
mentioning
confidence: 99%
“…The mechanism of action of LTX-109 represents a new and innovative bactericidal approach via a direct membrane disruption (17,18). The product has been shown not to be affected by cross-resistance to other available drugs and has demonstrated a low propensity for development of resistance (17,18,24). In the present study, a significant reduction of S. aureus CFU was demonstrated already after 2 days, although bacterial recurrence was observed in all but one subject 5 days after the end of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…LTX-109 is a broad-spectrum, fast-acting bactericidal antimicrobial drug that binds to negatively charged membrane components on the bacterial cell, which is followed by membrane disruption and cell lysis (17,18). Nonclinical and clinical studies have demonstrated that topical application of LTX-109 (1 to 5%) has a good safety profile and a low bioavailability (19).…”
mentioning
confidence: 99%